The perceptions of inpatients with schizophrenia about aggression: a qualitative study - Aydin, Adeviye; Kargin, Maral; Celebi, Evrim (Cumhuriyet Univ Tip Fak Psikiyatri Anabilim Dali, 2019)
Objective: Patients with schizophrenia may be at increased risk of aggressive behavior in relation to factors such as symptoms and severity of the disease. In this study, it is aimed to explore the thoughts and experiences of aggression in schizophrenia patients using a semi-structured interview questionnaire. Methods: Semi-structured individual interviews were conducted with 26 patients who had been hospitalized with a diagnosis of schizophrenia in Elazig Mental Health and Diseases Hospital. Interviews were recorded with voice recording and then transcribed. Content analysis was used in data analysis. Results: As a result of the analysis of the data obtained from the interviews, four themes were identified: aggressive behavior, feelings, consequences, suggestions. It was determined that consists of subthemes as 'violence', 'mental illness' for aggressive behavior theme; 'regret' for feelings theme; 'sent to prison, a closed service', 'death, wounding' and 'loss of hope' for consequences theme; 'treatment and rehabilitation', 'communication', 'spirit' and 'education', 'awareness' for suggestions theme. Conclusions: This study includes the physical, psychological and social reasons for the aggressive behaviors experienced in patients with schizophrenia, possible consequences and suggestions for preventing the occurrence of behavior. It is estimated that these results will enlighten on providing health care professionals and caregivers with the necessary support in sharing feelings in the management of the patient's aggressive behavior.
Yatarak tedavi gören şizofreni hastalarının saldırganlıkla ilgili algıları: Nitel bir çalışma
Keywords: aggression; schizophrenia; qualitative study